2012
DOI: 10.1371/journal.pone.0051431
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane Induces Learning Impairment That Is Mediated by Interleukin 1β in Rodents

Abstract: Postoperative cognitive decline is a clinical syndrome. Volatile anesthetics are commonly used during surgery. It is conceivable that volatile anesthetics may contribute to postoperative cognitive decline. Isoflurane can impair cognitive functions of animals under certain conditions. However, the mechanisms for this impairment are not clear. Here, male 18-month old Fisher 344 rats or 10-week old mice were exposed to 1.2 or 1.4% isoflurane for 2 h. Our studies showed that isoflurane impaired the cognitive funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
100
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 36 publications
9
100
0
Order By: Relevance
“…Neuroinf lammation contributes to volatile anesthetic-induced cognitive deficits and it has been demonstrated that isoflurane induces learning impairment by activating the NF-κB pathway and upregulating the expression of hippocampal interleukin-1β in rodents (39,40). Sevoflurane also increases levels of the pro-inflammatory cytokine interleukin-6 and tumor necrosis factor-α in the developing mouse brain (7).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinf lammation contributes to volatile anesthetic-induced cognitive deficits and it has been demonstrated that isoflurane induces learning impairment by activating the NF-κB pathway and upregulating the expression of hippocampal interleukin-1β in rodents (39,40). Sevoflurane also increases levels of the pro-inflammatory cytokine interleukin-6 and tumor necrosis factor-α in the developing mouse brain (7).…”
Section: Discussionmentioning
confidence: 99%
“…Isoflurane has been reported to induce neuroinflammation [5]. More notably, IL-1β is associated with isoflurane-induced cognitive impairment [5].…”
Section: Discussionmentioning
confidence: 99%
“…More notably, IL-1β is associated with isoflurane-induced cognitive impairment [5]. Elevated cytosolic Ca 2+ levels induced by isoflurane has been demonstrated to activate the NF-kB signalling pathway [24] that stimulates the activation of pro-inflammatory cytokines [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it does not require anesthesia, in contrast with sampling from the jugular vein or retroorbital sinus. When blood samples are collected surrounding behavioral procedures, administration of anesthetics is undesirable because it can interfere with learning and memory 4,5 . Second, it offers the ability to collect larger blood volumes than other venipuncture techniques, such as collection from the saphenous or dorsal pedal veins.…”
Section: Discussionmentioning
confidence: 99%